Plantation activities and ecosystem conservation: criteria and indicators for biodiversity conservation - Toma, T. (Organizing Comittee of the International Symposium/Workshop on the Kyoto Mechanism and the Conservation of Tropical Forest Ecosystem, 2004)
The paper is based on CIFOR's research achievements contained in the following two publications, "Fast wood forestry: myths and realities" by Cossalter and Pye-Smith and "Linking C&I to a code of practice for industrial tropical tree plantations" by Poulsen, Applegate and Raymond. One should consider all aspects of plantation when trying to measure their impacts on biodiversity. The two above-mentioned publications contain key information in this respect. "Fast Wood Forestry; Myth and Realities" discusses the main points of controverse related to forest plantations and sort out fact from fiction, truth from misinformation. The discussion on the links between fast wood plantations and biodiversity is summarized as follows: Plantation activities could do much to conserve biodiversity if they abided by a set of guiding principles. Impacts of plantation on biodiversity will be a function of what they replace. If a large swathe of natural forest is cleared to make way for a plantation, there will be a loss of biodiversity. The same applies when a natural savanna ecosystem is replaced by a plantation of alien species. Yet a similar plantation, established on degraded land, might bring about an increase in biodiversity. Other factors of importance include the location of the plantation, its size, length of rotation and species composition. The issue of contiguity is also important. If new plantations are sited close to existing natural forests, they may benefit from their biodiversity: animals, birds and insects will be readily available to invade the new plantations. However, if no such reservoir of biodiversity exists, then the chance of the plantations being invaded by wildlife from outside, and providing a new habitat, becomes more remote. It is worth bearing in mind that generalizations about the impact of plantations on the biodiversity, are often misleading. The problems related to plantations are often site-specific, and the way in which they are planned and managed is of paramount importance."Linking C&I to a Code of Practice for Industrial Tropical Tree Plantations" is a useful tool to improve plantation planning and managing. CIFOR's Criteria and Indicators (C&I) for Sustainable Development of Industrial Tropical Tree Plantations provides the benchmark for a plantation owner to assess progress towards sustainable forest management within their forest estate. The Code provides details on principles and minimum standards relating to improved plantation development and establishment. The CIFOR C&I and Code for Industrial Tropical Tree Plantations in relation to biodiversity conservation are formulated as follows: 1) Criteria: impact on structure and ecosystem function is minimized; 2) Indicators: exclusion and conservation zones are developed according to best practice; habitat trees are retained in plantation production areas where appropriate for wildlife; endangered flora and fauna on international (CITES) and country lists are protected; endangered endangered flora and fauna on local and regional lists are protected; 3)Code of practice: a) setting aside natural forest reserves within production areas large enough to maintain viable population of plants and animals particularly where rare and endangered; retaining areas of unlogged forest to maintain habitat diversity. b) These areas should connect patches of forest as corridors which will not be logged. c) retaining habitat trees in production areas where appropriate for wildlife; d) representation of forest types to be adequate reserved in conservation forests.